Rating of perceived exertion as a tool for prescribing and self regulating interval training: a pilot study - Ciolac, Emmanuel Gomes; Mantuani, Simone S; Neiva, Cassiano Merussi; Veradi, Carlos Eduardo Lopes; Pêssoa-Filho, Dalton Müller; Pimenta, Leonardo (Biology of Sport, 2015)
The aim of the present study was to analyse the usefulness of the 6-20 rating of perceived exertion (RPE) scale for prescribing and self-regulating high-intensity interval training (HIT) in young individuals. Eight healthy young subjects (age = 27.5±6.7 years) performed maximal graded exercise testing to determine their maximal and reserve heart rate (HR). Subjects then performed two HIT sessions (20 min on a treadmill) prescribed and regulated by their HR (HR: 1 min at 50% alternated with 1 min at 85% of reserve HR) or RPE (RPE: 1 minute at the 9-11 level [very light-fairly light] alternated with 1 minute at the 15-17 level [hard-very hard]) in random order. HR response and walking/running speed during the 20 min of exercise were compared between sessions.No significant difference between sessions was observed in HR during low- (HR: 135±15 bpm; RPE: 138±20 bpm) and high-intensity intervals (HR: 168±15 bpm; RPE: 170±18 bpm). Walking/running speed during low- (HR: 5.7±1.2 km · h -1 ; RPE: 5.7±1.3 km · h -1 ) and high-intensity intervals (HR: 7.8±1.9 km · h -1 ; RPE: 8.2±1.7 km · h -1 ) was also not different between sessions. No significant differences were observed in HR response and walking/running speed between HIT sessions prescribed and regulated by HR or RPE. This finding suggests that the 6-20 RPE scale may be a useful tool for prescribing and self-regulating HIT in young subjects.